Cote d'Ivoire : Sixth Reviews Under the Arrangement Under the Extended Credit Facility and the Extended Arrangement Under the Extended Fund Facility, and Request for Extension and Augmentation of Access; Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for the Cote d'Ivoire. (IMF Staff Country Reports; Country Report, 2019)
This paper discusses Cote d'Ivoire's Sixth Review Under the Arrangement of the Extended Credit Facility and the Extended Arrangement Under the Extended Fund Facility, and Request for Extension and Augmentation of Access. Cote d'Ivoire has been pursuing a development-oriented policy agenda, and the IMF-supported program in place since 2016 has supported that focus, paving the way for the private sector to become the main driver of growth. The performance under the program has been strong. The medium-term growth prospects remain robust, predicated on continuing prudent macroeconomic policy, furthering financial sector reforms and sustaining structural reforms to bolster private sector-led inclusive growth. Cote d'Ivoire's reform efforts have resulted in improvements in its business climate in recent years. It will be imperative to continue the reform agenda to further stimulate private sector activity and support inclusive growth, including by improving the energy sector, human capital and financial inclusion, accelerating digitalization, enhancing trade connectivity and governance, expanding the coverage of social safety nets, and reinforcing the statistical apparatus to help better inform economic policy.